2017
DOI: 10.1007/s12195-017-0487-6
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Role of Nesprin-1-Mediated Nucleus–Actin Filament Binding in Cyclic Stretch-Induced Fibroblast Elongation

Abstract: The intracellular mechanical link tethering the nucleus to the cytoskeleton has been suggested to be the linker of the nucleoskeleton and cytoskeleton (LINC) complex. Previous studies have reported that knockdown of nesprin-1, a component of the LINC complex that directly binds to actin filaments, suppresses cellular morphological response to mechanical stimuli. The relation between nesprin-1 knockdown and cellular morphological changes, however, remains unclear. In this study, we examined the mechanical role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…This suggested that silencing nesprin-1 could release the nucleus from the tension of F-actin filament, thus allowing for deformation before stretching. Also, fibroblastic cells manipulated with nesprin-1 siRNA showed decreased cell elongation under cyclic stretch [38].
Fig.
…”
Section: Sensing Mechanical Environments Through the Linc Complexmentioning
confidence: 99%
“…This suggested that silencing nesprin-1 could release the nucleus from the tension of F-actin filament, thus allowing for deformation before stretching. Also, fibroblastic cells manipulated with nesprin-1 siRNA showed decreased cell elongation under cyclic stretch [38].
Fig.
…”
Section: Sensing Mechanical Environments Through the Linc Complexmentioning
confidence: 99%
“…Nesprin-1 and Nesprin-2 are widely expressed, perform overlapping functions and contain large cytoplasmic spectrin-repeat domains with N-termini that bind to actin (Banerjee et al, 2014, Sakamoto et al, 2017, Zhou et al, 2018a. Nesprin-3 shares a similar KASH domain but its cytoplasmic region binds to plectin, mediating interactions with intermediate filaments (Wilhelmsen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The linker of the nucleoskeleton and cytoskeleton (LINC) complex is considered an important structure for endothelial cell adhesion and adaptation to shear stress and cyclic stretch (Denis et al, 2021). Nesprin-1, a component of the LINC complex that directly binds to actin filaments, suppresses cellular morphological responses to mechanical stimuli, and nesprin-1 knockdown induces more rounded cellular shapes than non-treated cells under both static and cyclic stretching conditions (Sakamoto et al, 2017). This indicates a reduction in the morphological response of endothelial cells to mechanical stimuli.…”
Section: Discussionmentioning
confidence: 99%